Book Review: Cyanobacteria as Environmental Determinants of Health - Aguilera, Anabella (2018)
This book is the result of the collaborative work between Argentinean researchers and the Ministry of Health who constituted the “Working Group on Health Effects of Cyanobacteria in Water” intended to raise the awareness concerning the increased occurrence of toxigenic cyanobacteria and the threats they pose (Provision 2/2011, Secretariat for Health Relations and Research). The synergy and collaborative interactions within this group have been key steps to promote the establishment of national guidelines for cyanobacterial blooms in drinking and recreational waters.